Deep Genomic Divergence and Phenotypic Admixture of the Treefrog Dendropsophus elegans (Hylidae: Amphibia) Coincide With Riverine Boundaries at the Brazilian Atlantic Forest - Pirani, Renata M.; Tonini, João F. R.; Thomaz, Andréa T.; Napoli, Marcelo F.; Encarnação, Lais C.; Knowles, L. Lacey; Werneck, Fernanda P. (Frontiers in Ecology and Evolution, 2022)
The Atlantic Forest biome (AF) is one of the Earth’s biodiversity hotspots, known for its high levels of species diversity and endemism. Factors related to palaeoenvironmental dynamics, such as the establishment of vegetational refugia and river basins, have different impacts on biological communities and biodiversity patterns in this biome. Here, we sample genome-wide RADseq data from a widespread treefrog (Dendropsophus elegans), inhabiting natural and human-impacted ecosystems at the Brazilian AF to test the impact of riverine boundaries and climatic refugia on population structure and diversification. We estimate divergence times and migration across identified genetic breaks related to the rivers Doce, Paraíba do Sul, Ribeira de Iguape, and Paraguaçu, known to represent barriers to gene flow for other AF endemic species, and test the role of climatic refugia. Finally, we investigate the impact of spatio-temporal population history on morphological variation in this species. We recovered a phylogeographic history supporting three distinct clades separated into two geographically structured populations, corresponding to the north and south of AF. In addition, we identified an admixture zone between north and south populations in the latitude close to the Doce River. Our findings support a pattern of isolation-by-distance and the existence of a secondary contact zone between populations, which might have been promoted by gene flow during population expansion. Further, we found support for models considering migration parameters for all the tested rivers with different population divergence times. Based on the species history and the AF palaeoenvironmental dynamics, we corroborate the role of forest refugia impacting population structure for this species through recent range expansion after the Last Glacial Maximum (LGM). The Doce and Paraíba do Sul Rivers coincide with the main genetic breaks, suggesting they might also have played a role in the diversification processes. Finally, despite finding subtle correlations for phenotypic data among different populations, variation is not strongly detectable and doesn't seem associated with speciation-level processes that could warrant taxonomic changes. Such results can be explained by phenotypic plasticity of the evaluated traits and by recent divergence times, where there has been insufficient time to accumulate enough phenotypic differences.